2017
DOI: 10.1093/sleep/zsx171
|View full text |Cite
|
Sign up to set email alerts
|

Limited Efficacy of Caffeine and Recovery Costs During and Following 5 Days of Chronic Sleep Restriction

Abstract: Caffeine appears to have limited efficacy for maintaining alertness and wakefulness across 5 days of sleep restriction. Perhaps more importantly, there may be recovery costs associated with caffeine use following conditions of prolonged sleep loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Figure shows the experimental mean RT data (orange dots with standard error bars) for each study (Doty et al., ; Kamimori et al., ; Mclellan et al., , ), as well as the UMP‐predicted mean RT profiles for the original studies (dashed orange lines) and the optimal dosing strategies (blue lines) that attempted to enhance neurobehavioural performance, using the same total amount of caffeine as in the original studies (Figure , red arrows). Overall, the UMP satisfactorily predicted the mean RT for the original studies (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure shows the experimental mean RT data (orange dots with standard error bars) for each study (Doty et al., ; Kamimori et al., ; Mclellan et al., , ), as well as the UMP‐predicted mean RT profiles for the original studies (dashed orange lines) and the optimal dosing strategies (blue lines) that attempted to enhance neurobehavioural performance, using the same total amount of caffeine as in the original studies (Figure , red arrows). Overall, the UMP satisfactorily predicted the mean RT for the original studies (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the optimal strategy prescribed more caffeine on later days (with the exception of the last day), owing to increasing sleep pressure, and allocated caffeine at the end of each of the first 4 days of CSR (Figure , blue arrows). Moreover, the optimal strategy did not prescribe caffeine early on the first day of CSR because performance impairment was mitigated by sleep banking (subjects spent 10 hr in bed on five previous nights) (Doty et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most sleep‐related studies have identified changes through short‐term sleep deprivation. Studies involving long‐term sleep deprivation (>3 days) have investigated the effect of caffeine on sleep . There are also studies that show that sleep quality is associated with obesity (body mass index, waist circumference, and fat percentage) .…”
Section: Introductionmentioning
confidence: 99%